LOCAL DYNAMICS OF SPORTS GROUPS - Oana RUSU; Demmys RUSU (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2011)
Approaching the group as a complex system seems the most adequate way for the investigative endeavourtargeting the sports groups. The complex dynamics of small social groups may be analyzed on three levels: at the locallevel, the internal activities of the group are analyzed; at the global level, the processes and emergent states of the groupare brought to attention; at the contextual level, the influences of certain factors (economic, cultural, social, political,etc.) may model the composition, coherence, as well as group behaviour. Inside of a sports group (at local level), byusing the group resources, the members of the group interact with each other, resulting in role structures and status, incomplex organization and communication systems, in agreement with the objectives of the group. The size of the sportsgroups is given by the regulations of the sports branches and it may influence the processes and relationships within thegroup. The typology, functions, and parameters of the sports group are determined by a series of criteria. The spatialdistribution of the members of a sports group, as well as the perception on the group territory may influence theefficiency and quality of the social relationships between the group members.